Background modeling and subtraction by codebook construction - Kyungnam Kim; Chalidabhongse, T.H.; Harwood, D.; Davis, L. (2004 International Conference on Image Processing, 2004. ICIP '04, 2004)
We present a new fast algorithm for background modeling and subtraction. Sample background values at each pixel are quantized into codebooks which represent a compressed form of background model for a long image sequence. This allows us to capture structural background variation due to periodic-like motion over a long period of time under limited memory. Our method can handle scenes containing moving backgrounds or illumination variations (shadows and highlights), and it achieves robust detection for compressed videos. We compared our method with other multimode modeling techniques.